2015
DOI: 10.1111/sode.12133
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Frequency and Severity of Bullying and Victimization in the Association with Empathy

Abstract: This study disentangled the frequency and perceived severity of experienced bullying and victimization by investigating their associations with cognitive and affective empathy. Participants were 800 children (7-12 years old) from third-to fifth-grade classrooms who completed self-report measures of the frequency and perceived severity of their bullying and victimization and of cognitive and affective empathy. Results showed that the frequency and perceived severity of bullying were moderately correlated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 62 publications
2
36
1
1
Order By: Relevance
“…An emerging body of the literature focuses on the association between bullying and empathy (i.e., see Eisenberg, Eggum, & Di Giunta, ; Joliffe & Farrington, ; Pozzoli et al ., ; Van Noorden, Bukowsi, Haselager, Lansu, & Cillessen, ; Van Noorden, Haselager, Cillessen, & Bukowski, ), although a growing body of studies has shown a negative association between empathy and defending behaviours in peer aggression and bullying (e.g., Barchia & Bussey, ; Gini et al ., ; Meter & Card, ; for a meta‐analysis, see Nickerson et al ., ). In addition, empathy has been linked with autonomous motivation for prosocial behaviour among adults (Gini, Pozzoli, & Vieno, ; Pavey et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging body of the literature focuses on the association between bullying and empathy (i.e., see Eisenberg, Eggum, & Di Giunta, ; Joliffe & Farrington, ; Pozzoli et al ., ; Van Noorden, Bukowsi, Haselager, Lansu, & Cillessen, ; Van Noorden, Haselager, Cillessen, & Bukowski, ), although a growing body of studies has shown a negative association between empathy and defending behaviours in peer aggression and bullying (e.g., Barchia & Bussey, ; Gini et al ., ; Meter & Card, ; for a meta‐analysis, see Nickerson et al ., ). In addition, empathy has been linked with autonomous motivation for prosocial behaviour among adults (Gini, Pozzoli, & Vieno, ; Pavey et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive empathy (four items) and affective empathy (four items) were measured toward each of the seven other children in the group. Items were selected from the adapted version of the Basic Empathy Scale (BES; Jolliffe & Farrington, )—which was used in Phase 1 as part of the larger project (van Noorden et al, )—and transformed to make the questionnaire target specific. For example, the cognitive item ‘I can understand my friend's happiness when she/he does well at something’ was transformed to ‘I can understand Child X 's happiness when she/he does well at something’; the affective item ‘I become sad when I see other people crying’ was transformed to ‘I become sad when I see Child X crying’.…”
Section: Methodsmentioning
confidence: 99%
“…This study consisted of two phases and was part of a larger project (van Noorden, Bukowski, Haselager, Lansu, & Cillessen, 2016;van Noorden, Haselager, Cillessen, & Bukowski, 2014;van Noorden, Haselager, Lansu, Cillessen, & Bukowski, 2015). In Phase 1, peer nomination data for bullying and victimization were collected in elementary school classrooms.…”
Section: Methodsmentioning
confidence: 99%
“…Last, though there is no established way to categorize the severity of bullying, van Noorden, Bukowski, Haselager, Lansu, and Cillessen (2016) found that in children who were bullied, frequency of bullying was not associated with perceived severity of bullying. For this reason, we chose to investigate whether the CDC's compendium of bullying assessment tools adequately measured the holistic experience of bullying.…”
Section: Limitationsmentioning
confidence: 97%